New street carnivore / Muhamad Amirin Zufayrie Abo Wahab ... [et al.] - Abo Wahab, Muhamad Amirin Zufayrie; Othman, Nurul Huda; Berahing, Muhammad Shahaidi; Mohd Syukri, Mastura; Ahmad Sabrey, Ahmad Mursyidie; Nur Fazil, Nur Fahmi (2016)
We serve meat that are cooked in various ways as in buffet style. Furthermore, we also have burger and satay set. The production or the cooking department of the business will always ensure that the chicken are in fresh condition and satisfy the needs and wants of customer. Besides, the department will also ensure only the best ingredients are used. New Street Carnivore Enterprise will also do the research and development process from time to time in order to fulfill needs and wants of the customer.